Characterisation of populations at risk of sub-optimal dosing of artemisinin-based combination therapy in Africa. - Abena Takyi; Verena I Carrara; Prabin Dahal; Marianna Przybylska; Eli Harriss; Genevieve Insaidoo; Karen I Barnes; Philippe J Guerin; Kasia Stepniewska (PLOS Global Public Health)
Selection of resistant malaria strains occurs when parasites are exposed to inadequate antimalarial drug concentrations. The proportion of uncomplicated falciparum malaria patients at risk of being sub-optimally dosed with the current World Health Organization (WHO) recommended artemisinin-based combination therapies (ACTs) is unknown. This study aims to estimate this proportion and the excess number of treatment failures (recrudescences) associated with sub-optimal dosing in Sub-Saharan Africa. Sub-populations at risk of sub-optimal dosing include wasted children <5 years of age, patients with hyperparasitaemia, pregnant women, people living with HIV, and overweight adults. Country-level data on population structure were extracted from openly accessible data sources. Pooled adjusted Hazard Ratios for PCR-confirmed recrudescence were estimated for each risk group from published meta-analyses using fixed-effect meta-analysis. In 2020, of the estimated 153.1 million uncomplicated P. falciparum malaria patients in Africa, the largest risk groups were the hyperparasitaemic patients (13.2 million, 8.6% of uncomplicated malaria cases) and overweight adults (10.3 million, 6.7% of uncomplicated cases). The estimated excess total number of treatment failures ranged from 0.338 million for a 98% baseline ACT efficacy to 1.352 million for a 92% baseline ACT efficacy. Our study shows that an estimated nearly 1 in 4 people with uncomplicated confirmed P. falciparum malaria in Africa are at risk of receiving a sub-optimal antimalarial drug dosing. This increases the risk of antimalarial drug resistance and poses a serious threat to malaria control and elimination efforts. Changes in antimalarial dosing or treatment duration of current antimalarials may be needed and new antimalarials development should ensure sufficient drug concentration levels in these sub-populations that carry a high malaria burden.